Effect of drought stress on protein and proline metabolism in seven traditional rice (Oryza sativa Linn.) genotypes of Assam, India - Chutia J; SP, Borah; B, Tanti (Journal of Research in Biology, 2012)
Abiotic stresses can directly or indirectly affect the physiological status of an organism by altering its metabolism, growth, and development. Many plant species naturally accumulate proline and protein as major organic osmolytes when subjected to different abiotic stresses. These compounds are thought to play adaptive roles in mediating osmotic adjustment and protecting sub cellular structures in stressed plants. Different approaches have been contemplated to increase the concentrations of proline like compounds in plants grown under stress conditions to increase their stress tolerance. Seven different traditional rice varieties of Assam were evaluated for their response to osmolyte production under physiological drought condition through simulation at three levels of osmotic stress of 0.15 bar, 0.25 bar and 0.56 bar of physiological drought initiated by polyethylene glycol (PEG 6000). Along with the evaluation for osmolyte response the different components of genotypic variation for six different drought-sustaining characters in the seven rice varieties were also substantiated. The results indicated that plant height and seed number have significant genotypic coefficient of variability (GCV) and heritability. Verities like Laodubi, Leserihali, Beriabhanga and Borah were screened out as the best drought sustaining variety